Examining reasons for irresponsible driving and improving the effectiveness of road safety interventions through social marketing. - Deng, Jiefang (2017)
This dissertation aims to examine the factors influencing the young driver to commit the distracted driving behavior especially from the individual perspectives. After reviewing the literature, the main factors can be divided into three types which are the threatening advertisement, individual factors and the social influence. This study has applied qualitative research method to collect the data and the data was generated from in-depth interviews conducted with 12 UK residents who possess the current driver licenses. The previous studies have largely focused on examining the effectiveness of the threatening advertisement in order to prevent this kind of irresponsible driving behavior, while the effects of using fear appeals are contentious. However, according to the implication of the previous researches, the personality and the ability of self-regulation could be the important indicators in preventing the distracted driving behavior but both of them are not well examined. Therefore, this research is trying to fill the research gap with purposes to specifically investigate the influence of personality and self-regulation in the distracted driving. The main findings identified by this study are supported by the previous research. The driving behavior of the young people is affected by the application of fear appeals in advertisements, individual perspectives (level of the awareness, the ability of self-regulation), social norms (parents and peer passengers). In addition, it is worthy to mention that the personality is not a key component in affecting the driving behavior in terms of the individual perspectives. However, the level of awareness and the ability of self-regulation are important determinants affecting their choice while driving. The findings have opened new directions for future study which is to improve young drivers’ awareness by establishing correct perceptions of driving and the distracted driving instead of strongly stressing to use fear appeals. Finally, managerial implications and limitations are discussed.